(3JGQjN GdOhd hGdedhcs - (3GHf GdaQGJ , eMeO Hf YHO GdQMje Hf Ydj Hf eMeO, fGUQ GdOjf GdMfaj,J (B807 (3g` s
(3ChdgG (B:s
(3jHJOF HMhGOK SfI (B501 (3Ke HhajGJgG s
(3BNQgG (B:s
(3jfJgi Edi MhGOK SfI (B511 s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdChds
(3QJH GdMhGOK ai JGQjNg Ydi GdSfjfs
(3GdfSNI Gdefbhdg YfgG gPg GdfSNI GdTeSjI ai edc TQa GdOjf MajO TjN GdESdGe RcQjG GdCfUGQi GdeJhai SfI (B1092 (3hYdjg NWg HPdcs
(3HChd cd eLdO agQS HNW GdYdGeI GdeQMhe JjehQ HGTGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B200 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B159s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B50 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B61 s
Keywords: (3GdJGQjNs